Distribuição quantum-caótica de chaves usando osciladores optoeletrônicos - Oliveira, Glaucionor Lima de (2018)
The first part of the present thesis brings optical setups based on optoelectronic oscillators for realization of key distribution, in optical networks, with security based on quantum physics and chaotic systems principles. Three optical setups are proposed: I) A setup for chaotic key distribution. II) A setup for quantum secured chaotic key distribution. III) A setup for quantum-chaotic key distribution, in which quantum and chaotic systems are integrated. In all cases the security analysis is realized. All three systems proved to be viable without the safest quantum-chaotic system. In the second part of the thesis, experimental aspects of photonic generation of microwave signals using fiber optical resonator are considered. Experiments for harmonic generation using amplitude and phase modulators in the optical loop were realized. It can be verified that the systems with phase modulators present a greater amount of harmonics generated.